Acupuncture versus rehabilitation for post-stroke shoulder-hand syndrome: a systematic review and meta-analysis of randomized controlled trials - Shi, Jinyuan; Chen, Fuyan; Liu, Yang; Bian, Mingtong; Sun, Xiaowei; Rong, Ru; Liu, Shuo (Frontiers in Neurology, 2025)
BackgroundShoulder-hand syndrome (SHS) is one of the common sequelae after stroke, which not only hinders the recovery of patients, but also increases the economic burden of the family. In the absence of effective treatment measures, acupuncture treatment has been widely used in China to treat post-stroke shoulder-hand syndrome, but the details are unclear. Therefore, this review aims to evaluate the true efficacy of acupuncture in patients with SHS.MethodsWe searched eight databases [PubMed, Embase, Web of Science, Cochrane library, China Biomedical Literature Database (CBM), China Science and Technology Journal (VIP) database, the China National Knowledge Infrastructure (CNKI) database, and Wan fang database] from its inception to March 2025, randomized controlled trials (RCTs) of SHS acupuncture treatment combined with rehabilitation (Rehab). Two investigators independently used pre-designed forms to extract valid data from eligible randomized controlled trials. Meta-analysis was implemented through the Rev. Man software (version 5.4). The strength of the evidence obtained was implemented using the GRADE profiler software. Adverse events (AEs) were collected by reading the full text and used to evaluate the safety of acupuncture treatment.ResultsForty-seven studies, involving 4,129 participants, met the eligibility criteria, and were included in the review. Overall meta-analysis showed that combined acupuncture rehabilitation significantly improved motor function (upper-limb Fugl-Meyer Assessment (FMA): 41 studies, mean difference (MD) 9.50, 95% confidence interval (CI) [8.47, 10.53]) and pain reduction (visual analog score (VAS): 37 studies, MD: −1.49, 95% CI [−1.66, −1.33]). It also improved activities of daily living (ADL) compared to rehabilitation alone (ADL: 17 studies, MD: 11.94, 95% CI [8.26, 13.63]). There was no significant difference in the occurrence of adverse events (AEs) between acupuncture treatment combined with Rehab and Rehab alone (p > 0.05). The certainty of the evidence was rated low level because of flaws in the study design and considerable heterogeneity among the included studies.ConclusionThis review found that acupuncture treatment combined with Rehab treatment may have a positive promoting effect on improving motor function, reducing pain, and improving daily living ability in SHS patients. However, due to the existing methodological quality issues, our findings should be treated with caution. Future high-quality studies are urgently needed to validate our findings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024536169.